2005
DOI: 10.1038/modpathol.3800487
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of p75 neurotrophin receptor (p75NTR) as a marker of breast myoepithelial cells

Abstract: We evaluated the low affinity neurotrophin receptor (p75 NTR ) as a marker of breast myoepithelial cells. Immunohistochemical staining for p75 NTR was performed on paraffin sections of 122 malignant breast lesions, 28 benign lesions and the adjacent normal breast tissue. The staining pattern was compared to those of myosin heavy chain and p63. p75 NTR immunostain was consistently positive and compatible with p63 and myosin immunoreactivity in the myoepithelial cells of the normal mammary gland, benign breast l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 21 publications
1
17
0
1
Order By: Relevance
“…Our findings suggest that the increases in expression seen in these two cancers are largely not mediated by genomic copy number change. The NGFR gene shows both genomic gain and loss in breast cancer cell lines, consistent with reports of variable expression (Aragona et al, 2001;Sakamoto et al, 2001;Davidson et al, 2004;Popnikolov et al, 2005;Reis-Filho et al, 2006).…”
Section: Pattern Of Genomic Changes Reflects Tumor Typessupporting
confidence: 77%
“…Our findings suggest that the increases in expression seen in these two cancers are largely not mediated by genomic copy number change. The NGFR gene shows both genomic gain and loss in breast cancer cell lines, consistent with reports of variable expression (Aragona et al, 2001;Sakamoto et al, 2001;Davidson et al, 2004;Popnikolov et al, 2005;Reis-Filho et al, 2006).…”
Section: Pattern Of Genomic Changes Reflects Tumor Typessupporting
confidence: 77%
“…CD271 has been described as a unique marker of melanoma stem cells in humans (24). However, its first description in breast attributed it as a marker of myoepithelial cells (16). More recent studies show that its overexpression strongly increases resistance to anti-tumoral TRAIL treatment (25).…”
Section: Discussionmentioning
confidence: 99%
“…MM was detected by the M18 antibody, which recognizes branched glycans (15), whereas CD271/p75 NTR was detected by the ME20.4 antibody (16). We show that frankly differentiated luminal-like cells without acquiring appreciable basallike traits can be aggressive and invasive when serially transplanted into NOD SCID gamma (NSG) mice or tested for invasiveness in Boyden chambers.…”
mentioning
confidence: 98%
“…In the breast, NGFR expression was found in myoepithelial cells in normal breast tissue as well as benign and preinvasive breast lesions 12 13. Provisional data suggested that NGFR identified a subgroup of basal-like breast cancers (BLBC) with good prognosis 13.…”
Section: Introductionmentioning
confidence: 99%